Audit Lingkungan pada Industri Manufaktur Tahu: Studi Kasus Pengelolaan Limbah Produksi Tahu pada Pabrik Tahu Kuring Pekanbaru - Roza Fitrialis; Nayla Riska Vania; Asrul Saleh Gea; Siti Rodiah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Tofu-manufacturing companies play an important role in local economies and food supply chains, yet many established production facilities still lack a formal environmental management system. This study examines the environmental management practices of Pabrik Tahu Kuring, a well-established tofu manufacturing company located on Jalan Harapan Raya, Pekanbaru, Riau, which has operated continuously since 2012. Using a descriptive qualitative case-study method, data were collected through in-depth interviews with the company's management and field observation of the production site. The findings show that the company maintains a stable production output, supported by nine employees, and regularly supplies tofu for the Free Nutritious Meal (Makan Bergizi Gratis/MBG) program in addition to routine market orders. Solid waste in the form of tofu dregs (ampas) is sold to livestock farmers, whereas liquid waste is discharged directly into a nearby river through a pipe without any prior treatment or wastewater treatment installation (IPAL). Environmental checks have occasionally been conducted internally, but not by a formal, independent environmental audit team, and no complaints from residents have been recorded to date. The main operational obstacle is the inconsistent market absorption of tofu dregs. The study recommends that the company establish a structured, periodic environmental audit mechanism and install a proper wastewater treatment facility commensurate with its production scale.